Pneumorrhachis as a complication of epidural anesthesia during the puerperium - Sarmiento-Piña, Maira (2024)
Epidural analgesia is a common procedure for pain relief, especially in obstetricpractice. Pneumorrhachis and pneumocephalus are rare complications ofunintentional dural puncture and injection of air into the subarachnoid or subduralspace. The presence of air within the spinal canal is a rare and usually benigncondition known as pneumorrhachis. The causes may be traumatic, non-traumaticor iatrogenic. Pneumorrhachis secondary to epidural anesthesia is associatedwith needle insertion using the loss of air resistance technique. Because it isusually asymptomatic and most cases with symptoms have non-focal neurologicalmanifestations, it is usually treated conservatively. This is because it usually resolvesspontaneously within hours or days. However, in some cases it may be related toserious underlying pathology and become symptomatic, requiring active diagnosisand treatment depending on the intensity of the symptoms. A case of pneumorrhachisas a complication of epidural anesthesia during the puerperium is presented.